Biomechanical differences of multidirectional jump landings among female basketball and soccer players - Taylor, J. B.; Ford, K. R.; Schmitz, R. J.; Ross, S. E.; Ackerman, T. A.; Shultz, S. J. (The Journal of Strength and Conditioning Research, 2017)
Anterior cruciate ligament (ACL) injury prevention programs are less successful in basketball than soccer and may be due to distinct movement strategies that these athletes develop from sport-specific training. The purpose of this study was to identify biomechanical differences between female basketball and soccer players during multidirectional jump landings. Lower extremity biomechanics of 89 female athletes who played competitive basketball (n = 40) or soccer (n = 49) at the middle- or high-school level were analyzed with 3-dimensional motion analysis during a drop vertical jump, double- (SAG-DL) and single-leg forward jump (SAG-SL), and double- (FRONT-DL) and single-leg (FRONT-SL) lateral jump. Basketball players landed with either less hip or knee, or both hip and knee excursion during all tasks (p = 0.05) except for the SAGSL task, basketball players landed with greater peak hip flexion angles (p = 0.04). The FRONT-SL task elicited the most distinct sport-specific differences, including decreased hip adduction (p < 0.001) angles, increased hip internal rotation (p = 0.003), and increased relative knee external rotation (p = 0.001) excursions in basketball players. In addition, the FRONT-SL task elicited greater forces in knee abduction (p = 0.003) and lesser forces in hip adduction (p = 0.001) and knee external rotation (p < 0.001) in basketball players. Joint energetics were different during the FRONT-DL task, as basketball players exhibited less sagittal plane energy absorption at the hip (p < 0.001) and greater hip (p < 0.001) and knee (p = 0.001) joint stiffness. Sport-specific movement strategies were identified during all jump landing tasks, such that soccer players exhibited a more protective landing strategy than basketball players, justifying future efforts toward sport-specific ACL injury prevention programs.